Divine Motherhood in Buddhist Iconography: The Religious Significance of Harithi in Gandhāra Art - Dr Qamar-un-Nisa (`, 2025)
The article explores the transformation and veneration of the goddess Harithi in Gandhāran Buddhist art. Originally depicted as a child-devouring Yakshini, Harithi undergoes a profound moral redemption through the Buddha’s compassion, emerging as a protector of children and a symbol of fertility and maternal care. The study examines her mythological origins, iconographic evolution, and socio-religious role within the syncretic cultural landscape of Gandhāra, where Greco-Roman artistic influences merged with Indian spiritual themes. Through detailed analysis of sculptural depictions, the article highlights Harithi’s nurturing imagery surrounded by children, adorned with symbols of abundance, and often paired with her consort Panchika reflecting her integration into monastic worship and her appeal to devotees, particularly women seeking fertility or protection against diseases like smallpox. The discussion also addresses the gendered dimensions of her iconography, noting the exclusivity of male children in her representations while acknowledging her subversion of patriarchal norms through her spiritual authority. By situating Harithi within broader South Asian traditions of maternal deities and comparative iconography, the article underscores Buddhism’s adaptive capacity to reinterpret indigenous fertility cults, offering a model of inclusivity and moral transformation. Keywords: Harithi, Gandhāra Art, Buddhist Iconography, Divine Motherhood, Fertility Goddess, Yakshini, Greco-Roman Influence, Moral Redemption, Gender, Syncretism